The potential of neglected and underutilized species for improving diets and nutrition - Hunter, D.; Borelli, Teresa; Beltrame, Daniela M.O.; Oliveira, C.N.S.; Coradin, Lídio; Wasike, Victor W.; Wasilwa, L.; Mwai, J.; Manjella, A.; Samarasinghe, Gamini W.L.; Madhujith, T.; Nadeeshani, H.V.H.; et al. (Springer, 2019)
Why have our food systems come to rely on such a narrow range of plant species of limited nutritional value? Today three staple crops (rice, maize and wheat) account for more than 50% of calories consumed while we continue to disregard the huge diversity of nutrient-rich plant species utilized by humanity throughout our history. The reasons for this situation are complex and challenging. Creative approaches are required to ensure greater integration of these plant species in agriculture and food systems, and ultimately greater food diversity on our plates and in our diets. This paper presents an overview of the nutritional value of select neglected and underutilized species (NUS) before describing in detail the work undertaken in four mega-diverse countries—Brazil, Kenya, Sri Lanka and Turkey—to increase the knowledge, appreciation, awareness and utilization of this nutrient-rich biodiversity encompassing both orphan crops and wild edible plant species. The paper highlights the novel and ingenious approaches these countries have used to prioritize a rich diversity of NUS for healthier diets and improved nutrition, and how this knowledge has been used to mainstream these plant species into production and consumption systems, including linking NUS to school meals and public food procurement, dietary guidelines and sustainable gastronomy. The paper concludes with some perspectives on the way forward for NUS and the community working on them (including researchers, universities and government agencies, national ministries, municipalities, producers, and civil society) in meeting the challenges of malnutrition and environmental sustainability in the 2030 sustainable development context.